Morphometric Measurements to Quantify the Cerulein Induced Hyperstimulatory Pancreatitis of Rats under the Protective Effect of Lectins - Ludwig Jonas; Ulrike Mikkat; Anke Witte; Uta Beckmann; Katrin Dölker; Heike Weber; Christian Hahnel; Günther Kundt; Horst Nizze (Analytical Cellular Pathology)
In preceding papers we demonstrated an inhibitory effect of wheat germ agglutinin (WGA) and Ulex europaeus agglutinin (UEA) on the cholecystokinin (CCK) binding to the CCK receptor of rat pancreatic cells and also on the CCK induced Ca2+ release and α-amylase secretion in vitro as well as on pancreatic secretion of intact rats in vivo. In the present study we show the same inhibitory effect of both lectins on the cerulein pancreatitis of rats. This acute pancreatitis was induced by supramaximal injections (5 µg/kg/h iv or 10 µg/kg/h ip) of the CCK analogue cerulein in rats every hour. To monitor the degree of pancreatitis, we measured the number and diameter of injury vacuoles in the pancreatic acinar cells as one of the most important signs of this type of pancreatitis by light microscopic morphometry with two different systems on paraffin sections. Furthermore, the serum α-amylase activity was measured biochemically. We found a correlation between the diameter of vacuoles inside the acinar cells and the serum enzyme activity up to 24 h. The simultaneous ip administration of cerulein and WGA or UEA in a dosage of 125 µg/kg/h for 8 h led to a reduction of vacuolar diameter from 13.1 ± 2.0 µm (cerulein) to 7.5 ± 1.1 µm (cerulein + WGA) or 7.2 ± 1.3 µm (cerulein + UEA). The serum amylase activity was reduced from 63.7 ± 15.8 mmol/l × min (cerulein) to 37.7 ± 11.8 (cerulein + WGA) or 39.4; +52.9; -31.1 (cerulein + UEA-I). Both parameters allow the grading this special type of pancreatitis to demonstrate the protective effect of the lectins.